A case of Fanconi syndrome as a complication of treatment with a checkpoint inhibitor in a patient with hepatocellular carcinoma - Mohammad Tinawi; Bahar Bastani (Society of Diabetic Nephropathy Prevention, 2020)
Introduction: Immune checkpoint inhibitors (CPIs) represent novel new cancer immunotherapy agents. The use of nivolumab has been linked with immune mediated acute interstitial nephritis (AIN). Case Presentation: We present the case of a patients with recurrent hepatocellular carcinoma who developed severe Fanconi syndrome, as evidenced by hyperchloremic metabolic acidosis, hypokalemia, hypophosphatemia, glucosuria, aminoaciduria, 8 months after initiating treatment with nivolumab, without any evidence of acute renal insufficiency. Conclusion: Clinicians need to be aware of the renal side effects of new novel cancer immunotherapy agents, such as, immune CPIs